Microwave assisted extraction of anthocyanin from purple sweet potato (Ipomoea batatas L.) using deep eutectic solvent (DES) based on citric acid - Evitasari, Rachma Tia; Rofiqoh, Hana; Damayanti, Putri Alfina; Chusna, Firda Mahira Alfiata (Jurnal Rekayasa Proses, 2022)
Purple sweet potato (Ipomoea batatas L.) is one of the tubers or roots that is widely grown in Indonesia that contain high antioxidants. One type of flavonoid that functions as an antioxidant is a natural dye called anthocyanin. In the process of extraction of anthocyanin, the solvent has an important role. In this research, the deep eutectic solvent was used because it is more economical and environmentally friendly. This research will optimize the microwave assisted extraction of anthocyanin content in purple sweet potato (Ipomoea batatas L.) using a deep eutectic solvent with the variation of material to solvent ratio, microwave power, and extraction time. Optimization is done by using the statistical method Response Surface Method (RSM) with Total Anthocyanin content as a response. The optimum operating conditions for the extraction of anthocyanins from purple sweet potato using the deep eutectic solvent were obtained at a solid to solvent ratio of 1:29 at a microwave power of 270 watts for 193 s, with an optimum TAC value of 311.64 mg/L and an antioxidant value of 44.85%. The use of DES can increase the extraction yield and is environmentally friendly.